MEDIA TANAM RAMAH LINGKUNGAN UNTUK PERSEMAIAN DI DESA KEUMUNENG PEUT KECAMATAN DARUL AMAN KABUPATEN ACEH TIMUR - Faiz Isma; Marai Heviyanti; Murdhiani; Dias Setianingsih; Irwansyah (Global Science Society, 2022)
Banda Mulia Subdistrict is one of the subdistricts in Aceh Tamiang Regency which is the center of shallot production in Aceh. Shallot production in Banda Mulia District reached 12.5 tons/ha. The Blessing Fried Onion Business Group is a business group engaged in the production of fried onions. The production process of fried onions is still done in a very simple way so that the production process takes a longer time. The goal to be achieved in this Community Empowerment Program is to provide assistance in the form of an onion peeling machine, an onion slicing machine, and a spinner machine. The specific target of this Community Empowerment Program activity is the development of fried onion micro businesses by utilizing technology in the production process to be able to improve the community's economy. In an effort to achieve these goals, the Community Empowerment Program team implemented several methods, starting with conducting surveys and direct interviews with the fried onion business group in order to obtain information on the main problems faced by partners. The Community Empowerment Team then provided assistance to partners by handing over the epidermis peeling machine, onion slicing machine and spinner machine so that the production process would be shorter.